Pengaruh Aktivitas Fisik Teratur terhadap Sistem Kekebalan Tubuh pada Wanita Atlet dan Non-Atlet - Yopie Yosua Saragih; Syebat Autarki Gulo; Nurhamidah Sari Siregar; Fauziah Nasution (Mutiara Pendidikan dan Olahraga, 2025)
Regular exercise plays a crucial role in maintaining and improving immune system function, especially in female athletes who experience hormonal and physiological stress during training. This review article aims to explain the effects of aerobic and anaerobic exercise on humoral immune parameters and stress hormone responses in female athletes compared to inactive women. Based on the results of various studies, moderate and consistent physical activity can increase levels of immunoglobulins (IgA, IgG, and IgM) and strengthen immune protection. On the other hand, high-intensity or excessive exercise can increase cortisol and ACTH levels, potentially suppressing immune function temporarily. Research findings also show that female athletes have a better immune profile compared to inactive women, as indicated by increased natural killer cell activity and lymphocyte proliferation. However, excessive exercise can lead to immunological imbalance. Therefore, moderate-intensity exercise and well-planned training programs are proven to maintain endurance and prevent the risk of immune decline. This review is expected to broaden the understanding of sports immunology and women's health.